Fast processing technique for tic coatings on titanium - Boonruang C. (2014)
Coatings of TiC on titanium by current heating technique was studied. The titanium rod was cut into the disks with about 20 mm diameter and about 1.5 mm thick. The disks were ground with SiC papers and polished with 0.05 μm alumina slurry, and then they were cleaned with acetone. In the coating process, titanium disks were placed amidst 20 mm diameter graphite powders pressed against them in the glass tube. The electric current was applied across the graphite matrix with the fixed electric powers from 100 to 180 W for 20 min in argon atmosphere. The titanium disks were characterized using XRD, SEM, EDS and microhardness tester. The coating temperature, mass change, carbon concentration and hardness increased as the applied electric power increased. TiC was detected on the titanium coated at 120 to 180 W The hardness of the titanium coated at 180 W is the highest at 6.53 GPa.